Ni(II), Zn(II), and Fe(III) complexes derived from novel unsymmetrical salen-type ligands: preparation, characterization and some properties. Issue 5 (30th June 2022) - Dilmen Portakal, Eylem; Kaya, Yeliz; Demirayak, Emire; Karacan Yeldir, Elif; Erçağ, Ayşe; Kaya, İsmet
Abstract: By using a half-salen ligand (HL) and substituted salicylaldehydes, new unsymmetrical salen-type ligands (H2 L 1, H2 L 2, and H2 L 3 ) and their Ni(II), Zn(II) and Fe(III) complexes were synthesized. The compounds were characterized based on elemental analysis, IR, 1 H NMR, X-ray diffraction (for HL), spectroscopy, mass spectrometry, magnetic moment, molar conductance measurements, and thermal analysis (TGA). The unsymmetrical salen ligands, during complexation, are attached to the metal by two imine nitrogen atoms and two phenolic oxygen atoms in all complexes; in the Fe(III) complexes, the fifth coordination is completed by chloride. Square planar geometry or distorted square planar geometry for [NiL 1-3 ], [ZnL 1-3 ], and square pyramidal geometry for [FeL 1-3 Cl] are proposed. Conductance measurements suggest non-electrolytic nature of the metal complexes. Thermogravimetric analysis showed that the complexes exhibit higher stability than the ligands. The electrochemical properties of the compounds were studied by cyclic voltammetry. HOMO-LUMO energy levels and electrochemical band gaps ( E′ g ) were calculated. The solid state electrical conductivity of the iodine-doped compounds was measured and their semiconductor properties were determined. In addition, fluorescence properties of ligands and Zn(II) complexes were investigated. Graphical Abstract: UF0001